Pengaruh Religiositas Dan Lingkungan Sosial Terhadap Minat Menabung Di Lembaga Keuangan Syariah Pada Karyawan Pt Jiale Indonesia - Ansori, Miswan; Kusuma, Dewa (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
Abstract This study aims to answer the question of whether religiosity and social environment influence the interest in saving at Islamic financial institutions among employees of PT Jiale Indonesia. The approach used in this research is quantitative, with primary data sources. Primary data were collected through an online questionnaire distributed to employees of PT Jiale Indonesia. The sampling method used is purposive sampling, with a total of 353 respondents. The analytical technique employed is multiple linear regression. The results of the study indicate that both religiosity and social environment influence the interest in saving at Sharia financial institutions. Among the two variables tested, the social environment variable has a greater influence on the interest in saving at Sharia financial institutions. REFERENSI Abduh, M., Alawiyah, T., Apriansyah, G., Sirodj, R. A., & Afgani, M. W. (2022). Survey Design: Cross Sectional dalam Penelitian Kualitatif. Jurnal Pendidikan Sains Dan Komputer, 3(01), 31–39. https://doi.org/10.47709/jpsk.v3i01.1955 Agarwala, R., Mishra, P., & Singh, R. (2019). Religiosity and consumer behavior: a summarizing review. Journal of Management, Spirituality and Religion, 16(1), 32–54. https://doi.org/10.1080/14766086.2018.1495098 Ajzen, I. (2012). The Theory of Planned Behavior. In P. A. M. Van Lange, A. W. Kruglanski, & E. T. Higgins (Eds.), Handbook of Theories of Social Psychology. London: SAGE Publications Ltd. Ajzen, I. (2020). The theory of planned behavior: Frequently asked questions. Human Behavior and Emerging Technologies, 2(4), 314–324. https://doi.org/10.1002/hbe2.195 Bitar, Z., Hallit, S., Khansa, W., & Obeid, S. (2021). Phubbing and temperaments among young Lebanese adults: the mediating effect of self-esteem and emotional intelligence. BMC Psychology, 9(1), 87–98. https://doi.org/10.1186/s40359-021-00594-7 Ghofur, A. (2018). Falsafah Ekonomi Syariah. Depok: Rajawali Press. Ghozali, I. (2018). Apliksi Analisis Multivariate dengan Program IBM SPSS 25 (9th ed.). Semarang: Badan Penerbit Universitas Diponegoro. Glock, C. Y. (1962). On The Study of Religious Commitment. Religious Education: The Official Journal of the Religious Education Association, 57(4), 98–110. Graafland, J. (2017). Religiosity, Attitude, and the Demand for Socially Responsible Products. Journal of Business Ethics, 144(1), 121–138. https://doi.org/10.1007/s10551-015-2796-9 Hadjar, I. (2021). Pendekatan Kuantitatif dalam Penelitian Agama. Semarang: Walisongo Press. Han, Z., Yeoh, E. K. K., & Wan Ahmad, W. M. B. (2018). Does Religious Obligation of Muslims In Western China Influence their Intention to Adopt Islamic Banking? Contemporary Chinese Political Economy and Strategic Relations, 4(3), 1207–1244. https://doi.org/https://icaps.nsysu.edu.tw/var/file/131/1131/img/2375/129599192.pdf Herawati, Z. R. (2023). Pengaruh Literasi Keuangan Syariah dan Lingkungan Sosial Terhadap Minat Penggunaan Layanan Bank Syariah (Studi pada Mahasiswa Perbankan Syariah UIN Malang) [Skripsi]. Universitas Islam Negeri Malang. Ibrahim, M. A., Fisol, W. N. M., & Haji-Othman, Y. (2017). Customer intention on Islamic Home Financing Products: An Application of Theory of Planned Behavior (TPB). Mediterranean Journal of Social Sciences, 8(2), 77–86. https://doi.org/10.5901/mjss.2017.v8n2p77 Ilyas, R. (2018). Analisis Sistem Pembiayaan Pada Perbankan Syariah. Adzkiya : Jurnal Hukum Dan Ekonomi Syariah, 6(1), 1–18. https://doi.org/10.32332/adzkiya.v6i1.1167 Iryani, R. M., & Kristanto, R. S. (2022). Pengaruh Pengetahuan Tentang Bank Syariah, Religiusitas, Lingkungan Sosial, Dan Uang Saku Terhadap Minat Menabung Mahasiswa Di Bank Syariah (Studi Kasus pada Mahasiswa STIE Bank BPD Jateng). Magisma: Jurnal Ilmiah Ekonomi Dan Bisnis, 10(2), 191–202. https://doi.org/10.35829/magisma.v10i2.228 Kasmir. (2014). Dasar-dasar Perbankan. Jakarta: Raja Grafindo Persada. Lucas, D. B., & Britt, S. . (2012). Measuring Advertising Effectiveness. New York: McGraw-Hill. Maghfiroh, S. (2018). Pengaruh Religiusitas, Pendapatan, dan Lingkungan Sosial Terhadap Minat Menabung Di Bank Syariah Pada Santri Pesantren Mahasiswi Darush Shalihat. Jurnal Pendidikan Dan Ekonomi, 7(3), 213–222. Obeid, H., & Kaabachi, S. (2016). Empirical investigation into customer adoption of Islamic banking services in Tunisia. The Journal of Applied Busines Research, 32(4), 1243–1256. https://doi.org/https://doi.org/10.19030/jabr.v32i4.9734 Ouafy, S. El, & Chakir, A. (2015). The Impact of Religiosity in Explanation of Moroccan Very Small Businesses Behaviour Toward Islamic Financial Products. IOSR Journal of Business and Management, 17(7), 2319–7668. https://doi.org/10.9790/487X-17727176 Pakaya, I., & Posumah, J. H. (2021). Pengaruh Lingkungan Sosial Terhadap Pendidikan Masyarakat Di Desa Biontong I Kecamatan Bolangitang Timur Kabupaten Bolaang Mongondow Utara. Jurnal Administrasi Publik, 7(104), 11–18. Retrieved from https://ejournal.unsrat.ac.id/v3/index.php/JAP/article/view/33692 Purwanto. (2018a). Fungsi Intermediary Bank Aceh Setelah Melakukan Konversi Menjadi Bank Umum Syariah. In Ihtifaz: Journal of Islamic Economics, Finance, and Banking (Vol. 1). https://doi.org/https://doi.org/10.12928/ijiefb.v1i1.248 Purwanto. (2018b). Teknik penyusunan instrumen uji validitas dan reliabilitas penelitian ekonomi syariah. Magelang: StaiaPress. Purwanto. (2019). Analisis Korelasi dan Regresi Linier dengan SPSS 21 (Panduan Praktis untuk Penelitian Ekonomi Syariah). Magelang: StaiaPress. Purwanto, P. (2021). Society attitudes and intentions to use products in sharia bank of Aceh : The role of religiosity and social influence. ABAC Journal, 41(2), 223–242. https://doi.org/http://www.assumptionjournal.au.edu/index.php/abacjournal/article/view/4223 Rahman, A., & Muktadir, M. G. (2021). SPSS: An Imperative Quantitative Data Analysis Tool for Social Science Research. International Journal of Research and Innovation in Social Science, 05(10), 300–302. https://doi.org/10.47772/IJRISS.2021.51012 Raihana, S., & Azhary, R. A. (2020). Pengaruh Pengetahuan, Religiusitas, Lokasi, Dan Lingkungan Sosial Terhadap Minat Menabung di Bank Aceh Syariah Cabang Jeuram (Studi Pada Masyarakat Kecamatan Seunagan Kabupaten Nagan Raya). JIHBIZ: Global Journal of Islamic Banking and Finance, 2(2), 110–123. Usman, H. (2016). Islamic religiosity scale, and its applied on the relationship between religiosity and selection of Islamic bank. Journal of Distribution Science, 14(2), 23–32. https://doi.org/http://dx.doi.org/10.15722/jds.14.2.201602.23 Vetter, T. R. (2017). Descriptive Statistics: Reporting the Answers to the 5 Basic Questions of Who, What, Why, When, Where, and a Sixth, So What? Anesthesia & Analgesia, 125(5), 1797–1802. https://doi.org/10.1213/ANE.0000000000002471